Age hardening and softening related to ordering and first and second grain boundary reaction in dental low carat gold alloy. (October 2013) - Jeong, J.-I.; Cho, S.-Y.; Lee, G.-Y.; Kwon, Y. H.; Kim, H.-I.; Seol, H.-J.
Abstract : A commercial dental Au–Ag–Cu–Pd alloy with small amounts of Ir and Zn was examined to elucidate the age hardening and softening mechanisms by characterising the phase transformation and microstructural changes via a first and second grain boundary reaction by means of a hardness test, X-ray diffraction study, field emission scanning electron microscopy and energy dispersive spectrometry. The hardness increased to the maximum value without an incubation period, and the overaging process showed a softening course in two steps. The increase in hardness was caused primarily by lattice distortion along the c axis due to the tetragonality of the metastable AuCu I′ and stable AuCu I phases, and secondarily by the coherence or semicoherence strain in the interfaces of the metastable AuCu I′ phase with the parent α 0, product α 1 and stable AuCu I phases. The fine lamellar forming first grain boundary reaction did not result in hardening, because it was not related directly to the phase separation process. The softening was in proportion to the quantity of lamellar structures by the first and second grain boundary reaction, and the softening effect of the fine lamellar forming first grain boundary reaction was larger than that of the coarse lamellar forming second grain boundary reaction.